A Micro‐Environment Regulator for Filling the Clinical Treatment Gap after a Glioblastoma Operation. Issue 3 (7th January 2022) - Zhang, Yiwen; You, Haoyu; Wang, Yaoben; Chen, Qinjun; Guo, Qin; Chu, Yongchao; Li, Chao; Zhou, Wenxi; Chen, Hongyi; Liu, Peixin; Wang, Yu; Zhao, Zhenhao; et al.
Abstract: The rapid postoperative recurrence and short survival time of glioblastoma (GBM) patients necessitate immediate and effective postoperative treatment. Herein, an immediate and mild postoperative local treatment strategy is developed that regulates the postoperative microenvironment and delays GBM recurrence. Briefly, an injectable hydrogel system (imGEL) loaded with Zn(II)2 ‐AMD3100 (AMD‐Zn) and CpG oligonucleotide nanoparticles (CpG NPs) is injected into the operation cavity, with long‐term function to block the recruitment of microglia/ macrophages and activate cytotoxic T cells. The finding indicated that the imGEL can regulate the immune microenvironment, inhibit GBM recurrence, and gain valuable time for subsequent adjuvant clinical chemotherapy. Abstract : Based on the current clinical dilemma of glioblastoma, this study describes a simple and mild postoperative local treatment strategy with clinical transformation prospects. Specifically, it is an injectable hydrogel system with the function of regulating the immune post‐operative micro‐environment to kill the residual tumor cells in the empty window period, which has gained valuable time for subsequent adjuvant treatment.